2011
DOI: 10.1111/j.1475-6773.2011.01354.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient–Physician Role Relationships and Patient Activation among Individuals with Chronic Illness

Abstract: Patient-physician relationships are an important factor in patients taking a more active role in their health and health care. Efforts to increase activation that focus only on individual patients ignore the important fact that the nature of roles and relationships between provider and patient can shape the behaviors and attitudes of patients in ways that support or discourage patient activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
144
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(163 citation statements)
references
References 26 publications
11
144
2
6
Order By: Relevance
“…Results should not be taken to indicate that PREMs can replace concrete health care quality metrics. The magnitude of associations between PREM scores and positive health care quality indicators may not be clinically meaningful; for instance, literature suggests that a 4-6 point difference in PAM scores is clinically meaningful, 41 but it did not reach this magnitude in our data. The relationship between our PREMs and health care quality metrics were relatively weak, however, previous research reporting congruence between PREMs and health care quality/safety has also reported similarly weak positive associations.…”
Section: Limitationscontrasting
confidence: 51%
“…Results should not be taken to indicate that PREMs can replace concrete health care quality metrics. The magnitude of associations between PREM scores and positive health care quality indicators may not be clinically meaningful; for instance, literature suggests that a 4-6 point difference in PAM scores is clinically meaningful, 41 but it did not reach this magnitude in our data. The relationship between our PREMs and health care quality metrics were relatively weak, however, previous research reporting congruence between PREMs and health care quality/safety has also reported similarly weak positive associations.…”
Section: Limitationscontrasting
confidence: 51%
“…41 Daniel Maeng and coauthors found that patients with higher scores and one or more chronic disease reported fewer problems with care coordination than did patients with lower scores. 42 Most of the studies looking at patient activation and patient experience are cross-sectional, which makes it impossible to know the direction of causality.…”
Section: Evidence Of Better Health Care Experiencesmentioning
confidence: 99%
“…The willingness to take an active part in his/her disease management is a major factor influencing adherence (van Ganse et al 2003). The physician's empathy, good interpersonal exchange, and greater fairness in the treatment process have led to higher levels of patient activation (Alexander et al 2012;Hojat et al 2011), while improved patient activation itself has been associated with higher medication adherence (Parchman et al 2010). Several studies have shown that appropriate patient education can help patients gain control over complex diseases (Casas et al 2006;Clark et al 2000;Smith et al 2008;Snow et al 2013;Sperl-Hillen et al 2011), to feel more independent from medical advice (Snow et al 2013), and leads to improved quality of life (Koff et al 2009).…”
Section: Enabling Treatment-related Behaviormentioning
confidence: 99%
“…An example of the different way of operationalization is how the concept of 'patient-doctor relationship' was assessed in different studies: while Kimberlin et al (2004) used focus group interviews to identify aspects of the doctor-patient relationship, other studies such as Little et al (2001) or Alexander et al (2012) used self-administered questionnaires, which sometimes have been previously validated and sometimes were pragmatically constructed for said trial. We therefore follow the argument of Di Blasi et al (2001): the results of a metaanalysis would have been like comparing apples with oranges.…”
Section: Strengths and Limitationsmentioning
confidence: 99%